Improvement Trends for Internal Combustion Engines - Albayrak Ceper, Bilge; Y?ld?z, Melih (IntechOpen, 2018)
Internal combustion engines have remained a challenge due to depending heavily on fossil fuels, which are already limited reserves, and a requirement for improvement in emission levels continuously. The number of advanced technologies such as hybrid systems and low-temperature combustion engines has been introduced, and a number of reports about the use of alternative fuels have been presented in recent years to overcome these challenges. The efforts have made the new concepts to be used in practical along with the new problems which are required advanced control systems. This book presents studies on internal combustion engines with alternative fuels and advanced combustion technologies to obtain efficiency and environment-friendly systems, measurement methodology of exhaust emissions and modelling of a hybrid engine system, and mechanical losses arising from ring-cylinder and ring-groove side contacts as well. The main theme here is to identify solutions for internal combustion engines in terms of fuel consumption, emissions, and performance.